2020
DOI: 10.18698/0236-3941-2020-2-76-87
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Geometric Features of the Peripheral Part of the Thin-Walled Spherical Segment on the Explosive Throwing Process

Abstract: The main factors controlling the formation of the stern of explosively formed projectiles are investigated using numerical calculations in a three-dimensional formulation of a problem. To form folds in the stern, it is proposed to use thin-walled spherical segments with a peripheral thickness deviation in terms of decreasing or increasing with respect to the thickness in the central part. The configurations of explosively formed projectiles with inclined folds in the stern are shown, and it is proposed to desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Li et al [12] investigated the feasibility of polygonal charge shell layers to form EFP with large aspect ratio and found that hexagonal polygonal charges can form EFP structures with better aerodynamic performance. Baburin et al [13] developed a model for forming a tilted-fold tail EFP, studied the influence of the tail on the change in the aerodynamic coefficients for a wide range of head-on angles, and calculated the angular velocity of the axial rotation of the tilted-fold tail EFP based on Newton's method. Ding et al [14] used stress-wave theory to analyze the long-rod fracture mechanism of explosively formed projectiles in the forming stage and experimentally verified the critical velocities of copper and tantalum foil forming.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [12] investigated the feasibility of polygonal charge shell layers to form EFP with large aspect ratio and found that hexagonal polygonal charges can form EFP structures with better aerodynamic performance. Baburin et al [13] developed a model for forming a tilted-fold tail EFP, studied the influence of the tail on the change in the aerodynamic coefficients for a wide range of head-on angles, and calculated the angular velocity of the axial rotation of the tilted-fold tail EFP based on Newton's method. Ding et al [14] used stress-wave theory to analyze the long-rod fracture mechanism of explosively formed projectiles in the forming stage and experimentally verified the critical velocities of copper and tantalum foil forming.…”
Section: Introductionmentioning
confidence: 99%